Post CAR T-cell therapy outcomes and management in HSCT-naive patients: a single-center experience - Phillips, Christine L.; Krupski, Christa; Khoury, Ruby; Dandoy, Christopher E.; Nelson, Adam S.; Galletta, Thomas J.; Faulhaber, Angela; Davies, Stella M.; Rubinstein, Jeremy D. (Frontiers in Hematology, 2023)
Background: Tisagenlecleucel (tisa-cel) is increasingly used in hematopoietic stem cell transplant (HSCT) naïve patients. Outcomes for HSCT following CAR-T cell therapies demonstrate low relapse rates, but, a significant portion of patients who receive tisa-cel can maintain remission without HSCT. Multiple factors are considered when choosing to proceed to HSCT Methods: We reviewed 31 patients who received tisa-cel at our institution who were transplant-naïve at the time of infusion. The aim was to determine rate and timing of consolidative HSCT, factors that led to HSCT and overall survival. Results: Three of 31 were non-responders to tisa-cel and ultimately died of disease. 12 of 28 responders remain alive with no evidence of disease (NED) without subsequent therapy. Of these patients, five of 12 had isolated extramedullary ALL (CNS=4, testes=1) and two of 12 had Down syndrome so no transplant was planned. In the remaining five of 12, close monitoring for signs of relapsed ALL using serial next-generation sequencing (NGS) MRD and lymphocyte subpopulation measurements was performed and due to continued negative findings no HSCT was chosen. Forty-three percent (12 of 28) responders ultimately proceeded to HSCT, with three receiving tisa-cel as planned bridge to HSCT due to CD22 negativity and/or provider preference (2 survived with NED); three proceeded to HSCT due to early loss of B-cell aplasia (BCA) (all survived with NED) and six had salvage HSCT following relapse (3 survived with NED, 1 alive in relapse). Three of 28 died following relapse post CAR-T without HSCT. The final patient had an isolated extramedullary soft tissue CD19+ relapse a year post tisa-cel, and is now NED without HSCT and persistent BCA. Conclusion: Close monitoring of NGS and B cell aplasia as well as consideration of site of disease can spare HSCT with maintenance of leukemia-free remission in a subset of patients, while still allowing for later HSCT in others. In our cohort, only a small subset of patients was unable to proceed to HSCT following relapse post CART.